Study of structure and physicochemical and mechanical properties in low-carbon steel after cyclic loading - Gorbachyov, L.A.; Pogrebnjak, A.D. (Науковий фізико-технологічний центр МОН та НАН України, 2009)
It has been determined by Auger-analysis method, roentgenofluorescence method, and the diffraction analysis that dark spots which appear in the examined steel under cyclic loading are new phases.